Pengaruh Promosi, Kualitas Pelayanan dan Store Atmosphere terhadap Minat Konsumen pada Coffee Shop Warkop Nonik Tulungagung - Nisa, Rois Khoirun; Hartiningtyas, Lativa Khoirun (BUDGETING : Journal of Business, Management and Accounting, 2023)
This study aims to examine the effect of promotion, service quality and store atmosphere coffee shop Warkop Nonik Tulungagung on consumer interest. In addition, it also aims to find out how much influence the promotion, service quality and store atmosphere coffee shop Warkop Nonik Tulungagung simultaneously have on consumer interest. This research approach is quantitative with the type of associative research. The sample of this research is Warkop Nonik Tulungagung consumers who have made purchases at Warkop Nonik. The analysis technique used is multiple linear regression analysis with a sample of 75 respondents using a closed questionnaire method. The results of data analysis and hypothesis testing show that service quality and store atmosphere have no significant effect on consumer interest. While promotions have a significant effect on consumer interest. Keyword : Custombers, Interest, Promotion, Promotion Store Atmosphere, Service Quality